A combined approach of convection-enhanced delivery of peptide nanofiber reservoir to prolong local DM1 retention for diffuse intrinsic pontine glioma treatment. Issue 10 (17th April 2020) - Bellat, Vanessa; Alcaina, Yago; Tung, Ching-Hsuan; Ting, Richard; Michel, Adam O; Souweidane, Mark; Law, Benedict
Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) is a highly lethal malignancy that occurs predominantly in children. DIPG is inoperable and post-diagnosis survival is less than 1 year, as conventional chemotherapy is ineffective. The intact blood–brain barrier (BBB) blocks drugs from entering the brain. Convection-enhanced delivery (CED) is a direct infusion technique delivering drugs to the brain, but it suffers from rapid drug clearance. Our goal is to overcome the delivery barrier via CED and maintain a therapeutic concentration at the glioma site with a payload-adjustable peptide nanofiber precursor (NFP) that displays a prolonged retention property as a drug carrier. Methods: The post-CED retention of 89 Zr-NFP was determined in real time using PET/CT imaging. Emtansine (DM1), a microtubule inhibitor, was conjugated to NFP. The cytotoxicity of the resulting DM1-NFP was tested against patient-derived DIPG cell lines. The therapeutic efficacy was evaluated in animals bearing orthotopic DIPG, according to glioma growth (measured using bioluminescence imaging) and the long-term survival. Results: DM1-NFP demonstrated potency against multiple glioma cell lines. The half-maximal inhibitory concentration values were in the nanomolar range. NFP remained at the infusion site (pons) for weeks, with a clearance half-life of 60 days. DM1-NFP inhibited glioma progression in animals, and offered a survival benefit (median survival of 62 days) compared with the untreated controls (28 days) and DM1-treated animal group (26 days). Conclusions: CED, in combination with DM1-NFP, complementarily functions to bypass the BBB, prolong drug retention at the fusion site, and maintain an effective therapeutic effect against DIPG to improve treatment outcome.